Chandra observations of the HII complex G5.89-0.39 and TeV gamma-ray source HESSJ1800-240B - Hampton, Elise J.; Wagner, Stefan (Arxiv, 2016)
We present the results of our investigation, using a Chandra X-ray observation, into the stellar population of the massive star formation region G5.89-0.39, and its potential connection to the coincident TeV gamma-ray source HESSJ1800-240B. G5.89-0.39 comprises two separate HII regions G5.89-0.39A and G5.89-0.39B (an ultra-compact HII region). We identified 159 individual X-ray point sources in our observation using the source detection algorithm wavdetect. 35 X-ray sources are associated with the HII complex G5.89-0.39. The 35 X-ray sources represent an average unabsorbed luminosity (0.3-10\,keV) of $\sim10^{30.5}$\,erg/s, typical of B7-B5 type stars. The potential ionising source of G5.89-0.39B known as Feldt's star is possibly identified in our observation with an unabsorbed X-ray luminosity suggestive of a B7-B5 star. The stacked energy spectra of these sources is well-fitted with a single thermal plasma APEC model with kT$\sim$5\,keV, and column density N$_{\rm H}=2.6×10^{22}$\,cm$^{-2}$ (A$_{\rm V}\sim 10$). The residual (source-subtracted) X-ray emission towards G5.89-0.39A and B is about 30% and 25% larger than their respective stacked source luminosities. Assuming this residual emission is from unresolved stellar sources, the total B-type-equivalent stellar content in G5.89-0.39A and B would be 75 stars, consistent with an earlier estimate of the total stellar mass of hot stars in G5.89-0.39. We have also looked at the variability of the 35 X-ray sources in G5.89-0.39. Ten of these sources are flagged as being variable. Further studies are needed to determine the exact causes of the variability, however the variability could point towards pre-main sequence stars. Such a stellar population could provide sufficient kinetic energy to account for a part of the GeV to TeV gamma-ray emission in the source HESSJ1800-240B.